The Importance of Location, Promotion, and Merchandising in Affecting the Consumer Purchasing Decision: A Case Study in PT Wijaya Motor Bandung, Indonesia - Dadang Suhairi (GoAcademica Research & Publishing, 2020)
The purpose of this study was to determine the effect of location, promotion and merchandising on consumer purchasing decisions at PT Wijaya Motor Bandung, Indonesia. This research method uses a quantitative approach. The data collected in this study used the distribution of questionnaires to 118 consumers at PT Wijaya Motor Bandung using a simple random sampling technique. The results of this study indicate that there is a positive and significant effect both partially and simultaneously between location, promotion and merchandising on consumer purchasing decisions at PT Wijaya Motor Bandung, Indonesia.